Expressions of Lithuanian Identity in the Spoken Language Corpus of Repatriated Children - Gaidienė, Anželika; Tamulionienė, Aurelija (Verbum, 2023)
The aim of the article is to analyse the spoken corpus samples with the lexemes Lietuva, lietuvis, lietuviškas and lietuviškai of the repatriated children and to show how the children's Lithuanian identity expressed through the use of these lexemes. The aim of the research was to explore the perception of Lithuania among the repatriated children, what they (dis)like in Lithuania, what characteristics of Lithuania, Lithuanians, etc., they identify, etc. The research material consists of data from 73 children (aged 8-12). Examples of these lexemes were collected from the first part of the semi-structured interview "warm-up", in which the pupils introduced themselves, talked about their family, friends, place of residence, etc. In this part of the interview, the children were also asked what they like in Lithuania, what they don't like and why. The analysis of the examples found showed that the Lithuanian identity of the repatriated children is most broadly expressed through social and cultural aspects. This significantly points to factors important for adaptation.
Keywords: repatriated children language; Lithuania; Lithuanian identity; corpus; aspect; etchnolinguistics